Peran Interaksi Simbolik dalam Perencanaan Komunikasi Pemasaran Restoran di Masa Pandemi (Studi Kasus Restoran Ta Wan Lippo Puri, Jakarta Barat) - Ramadhanti, Azizah Ayu; Pribadi, Muhammad Adi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The existence of the covid-19 pandemic in Indonesia has made Ta Wan Restaurant to undergo a renewal in terms of marketing strategy, so that a proper marketing communication plan is needed in order to get maximum turnover. The symbolic interaction at Ta Wan Restaurant plays an important role in the process of forming marketing communication planning because it is able to find out consumer desires in the midst of a pandemic so that it can meet consumer satisfaction and strongly support aspects of implementing employee performance every day. The method chosen by the researcher is a qualitative methodology with an exploratory type of case study method. Data was collected by non-participant observation, in-depth interviews with employees and consumers of Ta Wan Lippo Puri Restaurant, West Jakarta, document analysis, and literature study. The conclusion of this study, that there are six indicators of the success of marketing communication planning for Ta Wan Lippo Puri Restaurant, West Jakarta, including business objectives of making adequate profits, strategy renewal, tactics, implementation, monitoring and intensive evaluation. The symbolic interaction theory can help the process of forming a marketing communication plan for the Ta Wan Lippo Puri Restaurant in West Jakarta during the pandemic so that it can achieve the desired turnover. Adanya pandemi covid-19 di Indonesia membuat Restoran Ta Wan mengalami pembaharuan dari sisi strategi pemasaran, sehingga dibutuhkan sebuah perencanaan komunikasi pemasaran yang tepat agar mendapatkan omset yang maksimal. Interaksi simbolik pada Restoran Ta Wan berperan penting dalam proses pembentukan perencanaan komunikasi pemasaran karena mampu mengetahui keinginan konsumen di tengah masa pandemi sehingga dapat memenuhi kepuasan konsumen dan sangat mendukung aspek penerapan kinerja karyawan setiap hari. Metode yang dipilih peneliti adalah metodologi kualitatif dengan metode studi kasus jenis eksploratif. Pengumpulan data dilakukan dengan observasi non partisipan, wawancara mendalam dengan karyawan dan konsumen Restoran Ta Wan Lippo Puri Jakarta Barat, analisis dokumen, serta studi kepustakaan. Kesimpulan dari penelitian ini, yaitu terdapat enam indikator keberhasilan perencanaan komunikasi pemasaran Restoran Ta Wan Lippo Puri Jakarta Barat, meliputi tujuan bisnis membuat keuntungan yang memadai, pembaharuan strategi, taktis, implementasi, monitoring dan evaluasi intensif. Teori interaksi simbolik dapat membantu proses pembentukan perencanaan komunikasi pemasaran Restoran Ta Wan Lippo Puri Jakarta Barat selama pandemi sehingga berhasil mendapatkan omset yang diinginkan.